High speed parallel copper cable with stretch foamed insulation and method of processing the same
Patent Information
- Application Number
- CN202611215943.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0005]为了解决单一纯发泡层附着力低下以及现有异质绝缘发泡结构在高频段诱发电磁谐振的技术难题,本发明提供了一种兼顾高机械附着力与优良极高频传输平顺性的高速平行对铜缆及其制备方法
本发明基于极高频微波通信要求,构建了一套由“内致密、外多孔”构成的同构阶梯状介电基质。该结构采用了明确的功能分层原则:外层承担降低相对介电常数的功能,因此采用标准聚四氟乙烯;内层承担对金属表面的物理锚固作用,需在拉伸应力场中抑制成纤以保持实体连续性,因此采用具有较大立体空间位阻效应的全氟丙基乙烯基醚(PPVE)改性聚四氟乙烯。
Smart Images

Figure CN122716102B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of microwave radio frequency communication cables and polymer material extrusion processing technology, specifically relating to a high-speed parallel copper cable with a stretched foam insulation structure and its processing method. Background Technology
[0002] In the underlying physical architecture interconnection of modern cloud computing data centers and supercomputers, the Nyquist frequency for data transmission is increasing exponentially with the evolution of communication protocols. Under extremely high frequency alternating microwave radio frequency transmission, the skin effect driven by the alternating electromagnetic field causes a redistribution of the transmission paths of high-frequency carriers. The classical formula for the skin depth δ is defined as: Where ω is the angular frequency of the alternating electromagnetic wave. Where f is the operating frequency, μ is the absolute permeability of the material, and σ is the conductivity of the metallic conductor. From this formula, it can be deduced that in frequency bands as high as 56 GHz (corresponding to the fundamental frequency required for the 224 Gbps PAM4 modulation coding mechanism) and above, the actual effective transmission depth of electromagnetic wave energy and signals shrinks drastically to the submicron level. Its transmission energy field is highly concentrated on the most microscopic physical cross-section at the interface between the metallic conductor surface and the insulating dielectric material.
[0003] Under these electromagnetic boundary conditions, the equivalent relative permittivity of the insulating material Dielectric loss tangent Its three-dimensional physical uniformity becomes a determinant of high-frequency insertion loss (S). 21 The dominant variable is the difference in axial propagation time delay. Currently, the mainstream approach in the industry to reduce dielectric polarization loss and distributed capacitance is to introduce a low-dielectric-constant air phase into a microporous foam structure within a pure polymer insulating dielectric. This is based on the characteristic impedance physical model. Lowering the equivalent dielectric constant reduces the dielectric capacitance C, thereby maintaining impedance matching. However, in practical high-frequency broadband cable applications, after mechanical stretching and foaming, the effective physical adhesion area between the polymer matrix and the metal conductor decreases due to microfibrillation and opening within the polymer matrix, weakening its mechanical adhesion. Under conditions such as bending during installation or terminal crimping, the microporous insulation layer is prone to "core-pulling" defects, where it slips along the axial direction of the metal conductor. This minute displacement disrupts the characteristic impedance and electrical length symmetry in the microwave transmission line equation, causing mode conversion distortion.
[0004] Conventional processes often face a technical dilemma when addressing the mechanical adhesion defects of porous foam layers: introducing other heterogeneous functional resins into the insulation system can lead to impedance abrupt changes. The introduction of heterogeneous polymers not only increases manufacturing costs, but also causes differences in polarization relaxation times under alternating electromagnetic fields between different polymer structures. A step in the relative permittivity at the interface of heterogeneous materials can induce microwave energy reflection in specific frequency bands, resulting in significant microwave resonance dips on broadband transmission spectra. This limits the feasibility of smooth transmission in systems at 112 Gbps and higher frequencies. Summary of the Invention
[0005] To address the technical challenges of low adhesion of a single pure foam layer and electromagnetic resonance induced in the high-frequency band by existing heterogeneous insulating foam structures, this invention provides a high-speed parallel copper cable and its preparation method that balances high mechanical adhesion with excellent ultra-high frequency transmission smoothness.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention provides a high-speed parallel copper cable with a stretched foam insulation structure, comprising, from the inside out: Two parallel metal conductors; A dense inner layer is coaxially and directly coated on the surface of each of the metal conductors. The dense inner layer is a modified polytetrafluoroethylene dispersion resin fine powder extrusion prepared by emulsion polymerization. The modified polytetrafluoroethylene dispersion resin fine powder extrusion contains perfluoropropyl vinyl ether comonomer. The mass fraction of the perfluoropropyl vinyl ether comonomer in the main chain structure of the modified polytetrafluoroethylene macromolecule in the dense inner layer is between 0.3% and 1.5%. The main insulating layer is coaxially and directly wrapped around the outer surface of each of the dense inner layers. The main insulating layer is expanded polytetrafluoroethylene formed by co-extruding and wrapping it on the surface of the metal conductor together with the dense inner layer and inducing phase separation by mechanical longitudinal core stretching. Its microporous skeleton includes polytetrafluoroethylene crystal nodes that have not undergone plastic yielding and microfibers distributed along the tensile stress orientation. The dense inner layer and the main insulating layer have a continuous interface bonding region at the physical interface. The continuous interface bonding region is characterized by the two perfluorocarbon polymer matrices presenting an integrated and continuous molten bonding region at the physical interface without physical phase boundary breaks. A microporous wrapping layer that is spirally wound around and covers the outer periphery of two metal conductors with the main insulating layer on their outer surfaces; A metal shielding layer covering the outside of the microporous wrapping layer; and A polymer sheath layer extruded and coated on the outside of the metal shielding layer.
[0007] Furthermore, the overall porosity of the main insulating layer is between 33% and 80%, and the average micropore diameter defined by the crystal nodes and microfiber entities is limited to between 0.1 μm and 10.0 μm.
[0008] Furthermore, the metal conductor is an AWG 26 silver-plated oxygen-free copper single wire, the radial wall thickness of the dense inner layer is set between 0.01 mm and 0.05 mm; the radial wall thickness of the main insulation layer is set between 0.10 mm and 0.50 mm; and the peak adhesion force of the single-core axial slip pull-out between the physical interface of the dense inner layer and the metal conductor is between 5.5 N and 7.8 N.
[0009] Furthermore, the microporous wrapping layer is made of a microporous expanded polytetrafluoroethylene film that has undergone unidirectional or bidirectional stretching and orientation, and its porosity is set to 60% to 90%; the microporous wrapping layer is covered by a spiral overlapping wrapping method, and its interlayer wrapping overlap rate is set to the range of 15% to 50%.
[0010] Furthermore, the metal shielding layer is a metal foil strip with composite polyester insulating folds on one or both sides, which is wrapped in a spiral manner with a wrapping angle set to 15° to 45°, and the wrapping overlap rate between the shielding strip layers is between 15% and 30%.
[0011] Furthermore, at least one continuous exposed metal drainage ground wire is provided at the circumferential gap on the outside of the microporous wrapping layer; the outer diameter of the metal drainage ground wire is configured to be able to be embedded in the metal shielding layer under the assembly tension applied by the cable assembly machine, and the radial physical depth of the ground wire pressed into the porous body of the microporous wrapping layer is controlled to be 10% to 30% of the original radial total thickness of the microporous wrapping layer.
[0012] A second aspect of the present invention provides a method for high-speed parallel processing of the above-mentioned stretched foamed insulation structure with copper cable, comprising the following sequentially implemented steps: Step S1: Using a double-channel co-extrusion die equipped with a cross-head, a metal conductor with a uniformly preheated surface is introduced into the center of the die. A modified polytetrafluoroethylene dispersion resin paste containing liquid lubricant is extruded through the inner channel of the co-extrusion die to form an inner precursor. Simultaneously, a standard polytetrafluoroethylene dispersion resin paste containing liquid lubricant is extruded through the outer channel of the co-extrusion die to form an outer precursor. The two paste fluids converge at the die outlet sizing zone, and are co-extruded onto the continuously moving surface of the metal conductor to form a double-layer bonded unstretched insulating precursor wire. In this extrusion step, the ratio of the cross-sectional area of the extrusion die channel to the final cross-sectional area of the extruded tube is limited to between 100:1 and 200:1. Step S2: The unstretched insulated precursor wire is fed into the heating zone to allow the lubricant components inside the inner and outer precursor layers to fully evaporate, resulting in a dry double-layer polytetrafluoroethylene insulated wire. Step S3: The dried insulated wire is introduced into the stretching region within a constant temperature field. Longitudinal tensile tension is applied to the core wire by the difference in linear speed of the traction wheel group, so that the longitudinal stretching ratio is controlled between 1.5 and 5.0 times, and the strain rate is controlled between 50% / s and 150% / s. Under the above stretching conditions, the outer layer forms a porous structure, while the dense inner layer remains continuous throughout the stretching process. No obvious fracture phenomenon affecting subsequent sintering and performance is observed. Step S4: The stretched foamed wire is continuously introduced into a high-temperature sintering heat treatment zone with a temperature higher than the melting point of pure polytetrafluoroethylene (PTFE) crystal phase (327°C) under the external constraint of a constant axial tensile stress of 0.5 MPa to 5.0 MPa corresponding to the cross-section. In this heat treatment stage that exceeds the crystal phase critical point, the externally set axial stress forcibly suppresses the thermodynamic axial shrinkage of the porous microfiber PTFE skeleton. The dense inner layer and the foamed outer layer are heated at the physical interface, and the polymer segments of the two layers of materials undergo segment diffusion and entanglement in the gel state. After cooling, the matrix undergoes cross-linking and melting to form an integrated continuous structure. Step S5: The two insulated wire cores that have been cooled and shaped are brought together in parallel along the plane axis of symmetry. Then, the spiral overlapping wrapping of the microporous wrapping layer, the arrangement and embedding of the metal drainage ground wire, the overlapping wrapping of the metal shielding foil, and the extrusion molding of the outermost polymer sheath layer are completed in sequence.
[0013] Furthermore, in step S1, the liquid lubricant is defined as an aliphatic hydrocarbon solvent with an initial boiling point and a dry point between 150°C and 200°C, and the mass fraction of the lubricant in the polytetrafluoroethylene paste mixture is between 15% and 25%. If it is below 15%, the shear force during extrusion will be too high, which may cause the paste to break; if it is above 25%, the preform will not be able to maintain its morphological stability.
[0014] Furthermore, in step S4, the steady-state operating temperature of the high-temperature sintering zone is controlled between 350°C and 400°C, and the heat treatment residence time of the wire passing through the high-temperature sintering zone is controlled between 10 s and 30 s. This ensures that heat is conducted from the insulating surface to the dense inner layer close to the metal conductor and completes a sufficient phase transition, without causing dielectric embrittlement due to overheating.
[0015] Beneficial effects of this invention: Based on the requirements of ultra-high frequency microwave communication, this invention constructs a set of isomorphic stepped dielectric matrices consisting of a "dense inner layer and a porous outer layer". This structure adopts a clear functional layering principle: the outer layer is responsible for reducing the relative permittivity, therefore using standard polytetrafluoroethylene (PTFE); the inner layer is responsible for the physical anchoring of the metal surface, and needs to suppress fiber formation in a tensile stress field to maintain the continuity of the solid structure, therefore using perfluoropropyl vinyl ether (PPVE) modified PTFE with a large steric hindrance effect.
[0016] The dense inner layer and the outer porous foamed main insulating layer of this invention are both perfluorocarbon polymer macromolecules in terms of their chemical backbone, without any heterogeneous polymer intermediate transition layers such as polyperfluoroalkoxy ethers (PFA). This homocrystalline structure eliminates microwave impedance reflections introduced by the nonlinear step of the dielectric constant, effectively avoiding microwave resonance dips that may be induced in signal transmission, ensuring the smoothness of ultra-high frequency radio frequency transmission, and is suitable for the construction of physical links from 112 Gbps to 224 Gbps.
[0017] This invention utilizes a stress-constrained sintering process to achieve cross-linking and entanglement between the dense inner layer and the foamed main insulation layer when their melting points exceed 327°C. This results in an integrated, continuous region formed by the thermal fusion of two polytetrafluoroethylene (PTFE) layers, without any physical phase boundary breaks. This continuous interface region allows the mechanical shear force of the external porous skeleton to be conducted through the dense inner wall and anchored to the surface of the metal conductor, giving the foamed main insulation layer robust physical and mechanical adhesion and solving the problem of physical core pulling under bending conditions.
[0018] At the process control level, this invention designs a closed-loop process of "core-co-extrusion", "in-situ differential phase separation stretching", and "tension-constrained high-temperature sintering". Addressing the issue of longitudinal thermal shrinkage and collapse of high-porosity PTFE expanded structures when exceeding their crystalline melting point, this process applies axial tensile stress of 0.5 MPa to 5.0 MPa at the corresponding cross-section during the sintering stage using a servo system. This counteracts the thermodynamic shrinkage effect of the polymer chain segments, shaping micro-nano network pores at the microscale and inducing a more regular crystalline orientation of polymer microfibers along the axial direction. Attached Figure Description
[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0020] Figure 1 This is a schematic diagram of a high-speed parallel copper cable with a stretched foam insulation structure in an embodiment of the present invention.
[0021] Reference numerals: 1. High-speed parallel copper cable with stretched foam insulation structure; 11. Metal conductor; 12. Dense inner layer; 13. Main insulation layer; 14. Microporous wrapping layer; 15. Metal shielding layer; 16. Polymer sheath layer; 17. Metal grounding wire. Detailed Implementation
[0022] The present invention will be further illustrated by way of embodiments below, but the present invention is not limited to the scope of the embodiments described herein.
[0023] like Figure 1 As shown, this invention provides a high-speed parallel copper cable 1 with a stretched foam insulation structure, comprising two parallel metal conductors 11; a dense inner layer 12 coaxially and directly covering the surface of each of the metal conductors, wherein the dense inner layer 12 is a modified polytetrafluoroethylene dispersion resin fine powder extrusion prepared by emulsion polymerization, the modified polytetrafluoroethylene dispersion resin fine powder extrusion containing perfluoropropyl vinyl ether comonomer; and a main insulation layer 13 coaxially and directly covering the outer surface of each of the dense inner layers, wherein no heterogeneous polymer intermediate transition layer is provided between the dense inner layer 12 and the main insulation layer 13, and the two form direct physical contact at the microscopic physical interface; the main insulation layer 13 is connected to the dense inner layer 12. The inner layer 12 is coated on the surface of the metal conductor and formed by mechanical longitudinal core stretching to induce phase separation, resulting in expanded polytetrafluoroethylene. Its microporous skeleton includes unyielded polytetrafluoroethylene crystal nodes and microfibers distributed along the tensile stress orientation. The dense inner layer 12 and the main insulating layer 13 have a continuous interface bonding region at the physical interface, which is characterized by the two polytetrafluoroethylene layers forming a stable bond. A microporous wrapping layer 14 is spirally wound and covers the outer periphery of the two metal conductors with the main insulating layer on their outer surface. A metal shielding layer 15 covers the outside of the microporous wrapping layer. And a polymer sheath layer 16 is extruded and covers the outside of the metal shielding layer.
[0024] In some embodiments, the mass fraction of the perfluoropropyl vinyl ether comonomer in the dense inner layer modified polytetrafluoroethylene is between 0.3% and 1.5%. The overall porosity of the main insulation layer 13 is between 33% and 80%, and the average micropore diameter of the space defined by the crystal nodes and microfiber entities is limited to between 0.1 μm and 10.0 μm. The radial wall thickness of the dense inner layer 12 is set between 0.01 mm and 0.05 mm; the radial wall thickness of the main insulation layer 13 is set between 0.10 mm and 0.50 mm. Referring to the principle of the axial pull-out test method specified in test standard EIA-364-38D, under the test boundary conditions of using AWG 26 silver-plated oxygen-free copper single wire, with an ambient temperature of 25°C, an effective insulation peel length of 50 mm, and a constant tensile separation rate of 25 mm / min, the peak adhesion force of the single-core axial slip pull-out between the dense inner layer and the metal conductor physical interface is between 5.5 N and 7.8 N. The microporous wrapping layer 14 is made of a microporous expanded polytetrafluoroethylene film that has undergone unidirectional or bidirectional stretching and orientation, with a porosity of 60% to 90%. The microporous wrapping layer 14 is covered by a spiral overlapping wrapping method, with the interlayer wrapping overlap rate set between 15% and 50%. The metal shielding layer 15 is a metal foil strip with composite insulating folds on one or both sides, wrapped by a spiral wrapping method, with a wrapping angle set between 15° and 45°, and the wrapping overlap rate between the shielding strip layers is between 15% and 30%.
[0025] In some embodiments, at least one continuously exposed metal drainage ground wire 17 is provided at the geometric circumferential gap outside the microporous wrapping layer 14; the outer diameter of the metal drainage ground wire 17 is pre-configured to be embedded and engaged in the metal shielding layer 15 under the action of cable assembly tension, and the radial depth of the metal drainage ground wire 17 pressed into the interior of the microporous wrapping layer 14 accounts for 10% to 30% of the original total radial thickness of the microporous wrapping layer.
[0026] A method for high-speed parallel processing of the above-mentioned stretched foam insulation structure with copper cable includes the following sequentially implemented steps: Step S1: Using a double-channel co-extrusion die equipped with a cross-head, a metal conductor with a uniformly preheated surface is introduced into the center of the die. A modified polytetrafluoroethylene dispersion resin paste containing liquid lubricant is extruded through the inner channel of the co-extrusion die to form an inner precursor. Simultaneously, a standard polytetrafluoroethylene dispersion resin paste containing liquid lubricant is extruded through the outer channel of the co-extrusion die to form an outer precursor. The two paste fluids converge at the die outlet sizing zone, and are co-extruded onto the continuously moving surface of the metal conductor to form a double-layer bonded unstretched insulating precursor wire. In this extrusion step, the ratio of the cross-sectional area of the extrusion die channel to the final cross-sectional area of the extruded tube is limited to between 100:1 and 200:1. Step S2: The unstretched insulated precursor wire is fed into the heating zone to allow the lubricant components inside the inner and outer precursor layers to fully evaporate, resulting in a dry double-layer polytetrafluoroethylene insulated wire. Step S3: The dried insulated wire is introduced into the stretching region within a constant temperature field. Longitudinal tensile tension is applied to the core wire by the difference in linear velocity of the traction wheel set, so that the longitudinal stretch ratio is controlled between 1.5 and 5.0 times, and the strain rate is controlled between 50% / s and 150% / s. Under the above stretching conditions, the outer layer forms a porous structure, while the dense inner layer remains continuous throughout the stretching process. No obvious fracture phenomenon affecting subsequent sintering and performance is observed.
[0027] Step S4: The stretched foamed wire is continuously introduced into a high-temperature sintering heat treatment zone with a temperature higher than the melting point of pure polytetrafluoroethylene (PTFE) crystal phase (327°C) under the external constraint of a constant axial tensile stress of 0.5 MPa to 5.0 MPa corresponding to the cross-section. In this heat treatment stage that exceeds the crystal phase critical point, the externally set axial stress forcibly suppresses the thermodynamic axial shrinkage of the porous microfiber PTFE skeleton. The dense inner layer and the foamed outer layer are heated at the physical interface, and the polymer segments of the two layers of materials undergo segment diffusion and entanglement in the gel state. After cooling, the matrix undergoes cross-linking and melting to form an integrated continuous structure. Step S5: The two insulated wire cores that have been cooled and shaped are brought together in parallel along the plane axis of symmetry. Then, the spiral overlapping wrapping of the microporous wrapping layer, the arrangement and embedding of the metal drainage ground wire, the overlapping wrapping of the metal shielding foil, and the extrusion molding of the outermost polymer sheath layer are completed in sequence.
[0028] Further, in step S1, the liquid lubricant is defined as an aliphatic hydrocarbon solvent with an initial boiling point and a dry point between 150°C and 200°C, and the mass fraction of the lubricant in the polytetrafluoroethylene paste mixture is between 15% and 25%.
[0029] Furthermore, in step S4, the steady-state operating temperature of the high-temperature sintering zone is controlled between 350°C and 400°C, and the heat treatment residence time of the wire passing through the high-temperature sintering zone is controlled between 10 s and 30 s.
[0030] Example 1 Step S1 (Co-extrusion): Preheat the metal single wire (AWG 26 standard silver-plated oxygen-free copper wire with an outer diameter of 0.40 mm) to 150°C and introduce it into a double-channel co-extrusion die. The inner channel extrudes a paste containing 0.8% by mass of modified polytetrafluoroethylene (SSG designated 2.15) with perfluoropropyl vinyl ether (PPVE) and 15% by mass of isoparaffinic lubricant (IsoparH, initial boiling point 150°C), with a radial thickness set to 0.02 mm. The outer channel extrudes a standard pure polytetrafluoroethylene homopolymer paste (SSG designated 2.18, average particle size 500 μm) containing 15% lubricant, with a fluid radial thickness set to 0.35 mm. The compression ratio (RR) is set to 100:1.
[0031] Step S2 (Degreasing): The material is fed into a multi-stage stepped gradient heating furnace, where the ambient temperature is raised from 80°C to 200°C to evaporate the lubricant and obtain a dried blank.
[0032] Step S3 (Stretching): Entering the stretching zone maintained at 250°C, the core wire is subjected to a longitudinal mechanical stretch of 1.5 times through a precise linear speed difference set between the traction wheel sets, with the strain rate controlled at 50%. In this stage, the outer pure PTFE crystalline region undergoes intense tearing and evolves into a preliminary micro-nano pore network, with a measured porosity of 33%; while the inner layer, due to the obstruction of the PPVE side chains, does not undergo significant fibrillation fracture, maintaining the continuity of the solid.
[0033] Step S4 (Tension Constrained Sintering): While maintaining an axial tensile stress of 1.2 MPa, the in-situ foamed wire continuously passes through a heat treatment zone with a steady-state operating temperature of 350°C, with the residence time precisely controlled to 15 seconds. The high temperature exceeding the melting point of 327°C triggers mutual diffusion and melting of the inner and outer polymer interface layers. Due to the counterforce of the external 1.2 MPa axial stress, the skeleton does not undergo thermal shrinkage or collapse. After cooling, the two layers of material are thermosetting and solidified into an integrated continuous matrix without physical phase boundary faults.
[0034] Step S5 (Encapsulation): Two shaped wire cores are symmetrically parallel and joined together along their axial plane, and then spirally wound with an ePTFE film (with a porosity of 75%) using a wrapping machine, with an interlayer overlap of 25%. Subsequently, a silver-plated solid copper grounding wire with an outer diameter of 0.25 mm is implanted in the circumferential valley. An aluminum foil composite tape with a 25° inclination is then used as a spiral shielding layer on the outside, with a wrapping overlap of 25%. Finally, a high flame-retardant polymer sheath is extruded. Microscopic cross-sectional examination shows that the radial depth of the grounding wire pressed into the porous solid of the microporous wrapping layer accounts for 12%.
[0035] Example 2 In step S1, the proportion of lubricating solvent in the paste is increased to 20%, the inner layer extrusion thickness is set to 0.03 mm, the main insulation thickness is set to 0.30 mm, and the extrusion compression ratio is increased to 150:1. In step S3, the temperature of the stretching zone is raised to 280°C, a longitudinal mechanical stretch of 3.5 times is applied, the strain rate is accelerated to 100% / s, and the outer layer porosity is stabilized at 71%. In step S4, the temperature of the sintering zone is increased to 380°C, and the synchronous matching tensile stress is 1.5 MPa. The physical indentation depth of the drainage ground wire is 22% when the encapsulation slice is inspected. The remaining parameters and steps are the same as in Example 1.
[0036] Example 3 In step S1, the co-extrusion compression ratio was set to 200:1. In step S3, the temperature of the stretching zone was increased to 320°C, and a mechanical stretch of 5.0 times was applied at a strain rate of 150% / s, increasing the outer layer porosity to 80%. In step S4, the high-temperature sintering zone was set at 400°C, and a tensile stress of 2.0 MPa was applied to resist thermal shrinkage stress. Final cable fabrication and cross-section analysis showed that the grounding wire penetration depth was 28%. The remaining parameters and steps were the same as in Example 2.
[0037] Example 4 Using the same material configuration as in Example 2, step S3 applied a 2.5-fold longitudinal stretch, resulting in a porosity of 58%. The key step, S5, involved spiral winding of a densified ePTFE film with a porosity set to 60% and an interlayer overlap rate of 15%. An aluminum foil composite strip with a 15° angle was used as the metal shield, with an interlayer overlap rate of 15%. All other parameters and steps were the same as in Example 2.
[0038] Example 5 Using the configuration of Example 2, step S3 applied a longitudinal stretch of 4.2 times, and the porosity test result was 75%. In step S5: an ultra-foamed ePTFE film (porosity approximately 90%) was used for wrapping, with a 50% wrapping overlap rate to increase the elastic buffer thickness of the insulation outer diameter. The spiral wrapping angle of the metal foil strip was increased to 45°, and the overlap rate was set to 30%. The remaining parameters and steps were the same as in Example 2.
[0039] Example 6 Based on the process of Example 2, in step S1, the mass fraction of perfluoropropyl vinyl ether (PPVE) in the modified polytetrafluoroethylene extruded into the inner flow channel is set to 0.3%. The remaining parameters and steps are the same as in Example 2.
[0040] Example 7 Based on the process of Example 2, the mass fraction of PPVE in the modified resin supplied to the inner flow channel was set to 1.5%. The remaining parameters and steps were the same as in Example 2.
[0041] Example 8 Based on the process of Example 2, the mechanical traction tension is reduced in step S4, and the equivalent axial tensile stress is 0.5 MPa. Simultaneously, the linear speed is increased, shortening the residence time of the cable in the high-temperature treatment zone (380°C) to 10 s. The remaining parameters and steps are the same as in Example 2.
[0042] Example 9 Based on the process of Example 3, a higher external tensile torque is applied in step S4, with an equivalent axial tensile stress of 5.0 MPa. By slowing down the linear velocity of the traction system, the residence time in the thermal field is extended to 30 s. The remaining parameters and steps are the same as in Example 3.
[0043] Comparative Example 1 The same two-layer co-extrusion process as in Example 2 was maintained, except that the inner material of the co-extrusion was replaced with a conventional polyperfluoroalkoxy ether (PFA) heteropolymer resin with a melt flow rate (MFR) of 30 g / 10 min. The outer PTFE of the wire was stretched and foamed to a porosity of 71%. The remaining parameters and steps were the same as in Example 2.
[0044] Comparative Example 2 The same physical parameters as in Example 2 were used, but the inner layer feed material was replaced with pure PTFE homopolymer dispersion resin (SSG 2.18) without added PPVE monomer. Subsequent mechanical stretching was performed at 3.5 times the boundary of Example 2. All other parameters and procedures were the same as in Example 2.
[0045] Comparative Example 3 Using the same foaming process as in Example 2, in the 380°C sintering stage of step S4, the external mechanical traction tension constraint is released, so that the axial tensile stress is reduced to 0 MPa.
[0046] Comparative Example 4 Based on the parameters of Example 2, the winding tension of the cable drainage ground wire was reduced in the post-processing step, so that the depth of the ground wire pressed into the outer micro-perforated wrapping layer was only 3%. The remaining parameters and steps were the same as in Example 2.
[0047] Comparative Example 5 The parameters were the same as in Example 2, but in step S4, during the interface shaping stage, the heat treatment temperature was lowered to 300°C (below the 327°C melting point of polytetrafluoroethylene molecules). The tensile stress was kept constant during the test. The remaining parameters and steps were the same as in Example 2.
[0048] Comparative Example 6 Based on the parameters of Example 2, the mass fraction of PPVE in the modified resin constituting the dense inner layer was increased to 2.5%. This comparative example aims to verify the effect of excess modified comonomer on polymer crystallinity and ultra-high frequency dielectric loss performance. The remaining parameters and procedures are the same as in Example 2.
[0049] Performance experiments were conducted on the copper cables prepared in the examples and comparative examples. The parameters in the test data results table were obtained using the following highly reproducible inspection and calculation methods: (1) Average micropore diameter test: The average micropore diameter of the main insulation layer was measured using a capillary flow pore size analyzer (POROLUX type pore size analyzer) according to ASTM F316-03 standard. During the test, the porous tubular sample of the peeled main insulation layer was first immersed in a test liquid with known surface tension and intrinsic wettability (perfluoropolyether wetting agent, surface tension of 16.0 mN / m) to completely wet it. Then, nitrogen was used as the exhaust gas, and the wetting liquid was discharged from the micropores of the porous skeleton according to the pressurization flow rate mode from low to high. The response curve of the gas exhaust flow rate and pressure was measured, and the dry curve of the sample under dry condition was measured simultaneously. The average flow pore diameter was calculated by the built-in system of the instrument and used as the average micropore diameter of the main insulation layer described in this application.
[0050] (2) Equivalent relative permittivity Delay drift and S 21 Insertion loss test: A Keysight PNA-X vector network analyzer (scanning range from 10 MHz to 110 GHz) was used with a precision coaxial crimp test fixture for frequency sweeping. Before testing, the network analyzer was calibrated using a standard calibration kit to perform a full two-port SOLT (short-circuit-open-load-straight) calibration to eliminate systematic errors introduced by the cable and built-in system channels. A 3.0 m long high-speed parallel-pair copper cable sample was terminated at both ends to the test fixture, and the frequency domain scattering parameter S was obtained. 21 Insertion loss transmission spectrum. Equivalent relative permittivity. Based on the absolute propagation delay t of the high-frequency signal at the 56 GHz Nyquist frequency. d The conversion yields the following calculation formula:
[0051] In the formula, is the equivalent relative permittivity at 56 GHz; c is the speed of light in vacuum (taken as 3.0 x 10⁻⁶). 8 m / s); t d The single-end physical transmission delay (in seconds) is measured by a vector network analyzer; L is the absolute physical length of the test sample (taken as 3.0 m here).
[0052] (3) Single-core axial slip pull-out peak adhesion (pulling force extreme value) test: Referring to the tensile and shear principles of mechanical testing, a precision electronic tensile testing machine was used in conjunction with a specially designed self-made perforated shear fixture for measurement. A single-core cable sample with a total insulation length of 50 mm was prepared, and one end was partially stripped to expose a 10 mm long bare metal conductor. The test fixture included a fixed steel plate with a 0.42 mm diameter perforation at its center (the perforation diameter is 0.40 mm larger than the outer diameter of the inner metal conductor and smaller than the set outer diameter of the dense inner layer). During testing, the exposed copper conductor end of the sample was passed downwards through the perforation of the fixed steel plate, so that the outer end face of the unstripped insulation layer of the sample was against the bearing surface of the fixed steel plate. The lower clamp of the tensile testing machine axially clamped the drooping bare copper conductor, and then the tensile testing machine was started, causing the lower clamp to move downwards at a constant separation tensile rate of 25 mm / min. The maximum force value at which relative slippage occurred between the metal conductor and the dense inner layer interface was measured and recorded as the slippage pull-out peak adhesion force.
[0053] (4) Porosity test of the main insulation layer: The apparent density of the insulating primary layer, expanded PTFE sheath, was precisely measured and compared with the solid reference density of dense PTFE. The specific calculation formula is as follows:
[0054] In the formula, P is the porosity of the main insulating layer; ρ apparent The apparent density of the stripped main insulation layer expanded tubular sheath is calculated by weighing the main insulation layer sheath of known length using a 0.01% electronic balance and dividing it by the total volume obtained by multiplying the cross-sectional area by the length using a precision optical projection microscope; ρ solid The intrinsic specific gravity of dense polytetrafluoroethylene is taken as 2.18 g / cm³.
[0055] Test data results table
[0056] A comprehensive mechanistic analysis of the above results: 1. Based on rheology and phase separation principles, as the mechanical tensile tension ratio is gradually increased from 1.5 times (Example 1) to 5.0 times (Example 3), the physical porosity (volume fraction P) of the generated ePTFE main insulation layer increases from 33% to 80%. A large number of dry air molecules with polarizability close to that of a vacuum state (relative permittivity of approximately 1.0) are fixed and encapsulated within a network constructed of polymer three-dimensional microfibers and nodes. This structural expansion results in a measured overall equivalent relative permittivity of the transmission cable at 56 GHz (corresponding to the core Nyquist fundamental frequency of future 224 Gbps PAM4 modulation). It decreased from 1.76 to 1.40. According to the mathematical integral relationship of distributed capacitance, C∞ This significantly reduces the interphase and ground coupling parasitic capacitance reactance between parallel differential pair transmission lines. This allows electromagnetic wave energy to propagate through the matrix in a minimally depleted state while maintaining a specific external physical impedance (e.g., a constant nominal 100 Ω), macroscopically manifested as a significant reduction in microwave RF high-frequency insertion loss and a stable lower limit for propagation time difference in the embodiments.
[0057] 2. Comparing the data in the table, the extreme value of slip pull-out corresponding to Example 1 (low porosity 33%) is 7.8 N; when the stretching amplitude increases dramatically, causing the porosity to rise to a peak of 80% (Example 3), the corresponding axial pull-out adhesion force drops to 5.5 N. This phenomenon indicates that, under the geometric measurement conditions of the cross-sectional perimeter and the fixed axial calibration length (10 mm) of the metal conductor, the increase in pore volume in the expanded porous layer inevitably leads to a decrease in the actual effective contact integral area between the dense perfluorocarbon polymer macromolecule and the underlying microscopic copper metal lattice surface, where Coulomb interaction and mechanical intermolecular interlocking can occur. The reduction in the solid contact area results in a decrease in the values of the macroscopic shear stress and macroscopic blocking yield pull-out resistance. However, in this invention, thanks to the presence of an extremely thin yet exceptionally tough micron-sized dense inner layer with steric hindrance (the addition of PPVE inhibits fibrillation), even when covered by an extremely loose skeleton with 80% ultra-high foaming, a macroscopically integrated continuous matrix spanning the bilayer molecular phase boundary is formed during the high-temperature eutectic gel window exceeding 327°C (eliminating structural discontinuities). Therefore, although the adhesion strength decreases somewhat, it remains above 5.5 N. In Comparative Example 2 (using only standard pure powder without monomer modification as the inner wall), under the same strong external force, it undergoes fiber-forming tearing and structural disintegration, resulting in adhesion strength dropping to 1.5 N, which leads to "core-pulling" short circuits when encountering winding tension. When PPVE monomer is added in excess to 2.5% (Comparative Example 6), although fibrillation is inhibited, the intrinsic crystalline network of polytetrafluoroethylene is excessively damaged, leading to a significant decrease in the cohesive strength of the dense inner layer itself. When subjected to tensile shear force, the inner layer material itself undergoes yield fracture rather than interfacial peeling, so the macroscopic tensile force actually drops back to 5.2 N.
[0058] 3. As can be seen from the skin depth formula and characteristic impedance Z0 physical model mentioned above, when the radio frequency operating frequency exceeds gigahertz or even moves towards tens or hundreds of gigahertz, the electromagnetic field propagation boundary and medium homogeneity become more stringent regarding phase angle deviation. Current conventional techniques, as shown in "Comparative Example 1," involve coating the interface between copper and foamed insulating material with a low-melting-point PFA (polyfluoroalkoxy ether) or even FEP heteropolymer adhesive as a transition bonding layer. However, data shows that PFA not only suffers from higher dissipative dielectric losses due to intrinsic dipole moment deviation, but also, at the submicron and micron scales, this heterogeneous transition interface causes a nonlinear step-like dielectric constant change along the radial direction of electromagnetic wave propagation (i.e., across the interface normal). Based on impedance transmission derivation and the principle of microwave echo reflection, dielectric steps cause discontinuities in the characteristic wave impedance. In wavelength-matched 92 GHz and other harmonic bands, this induces severe standing waves and high-energy microwave resonant reflections exceeding 5.0 dB (suck-out reflections). However, in all embodiments of this invention (1 to 9), the used material is a homocrystalline PPVE modified copolymer powder derived from the main insulating pure PTFE. Even with the addition of trace amounts of ether side chain branches (limited to 0.3% to 1.5%) to provide steric hindrance, the large perfluorocarbon macromolecular chemical backbone remains unchanged, and the molecular polarization relaxation period maintains a nearly smooth transition in sync with the dielectric equivalent relaxation time constant. Therefore, in the Smith chart full-frequency domain network sweep diagram spanning from 0 to 110 GHz, the inducing S... 21 The dielectric transition exhibits a deep dip in the transmission spectrum, with a smooth and uniform curve. In Example 9, due to the application of an ultra-high axial tensile external torque of up to 5.0 MPa to the high-speed traveling wire, and the limitation of a deep melting residence time of up to 30 s under an extreme thermal field of 400°C, the porous framework underwent excessive longitudinal extension, inducing a Poisson contraction effect at the microscale. Some radial pores closed and melted due to transverse compressive stress, resulting in a slight decrease in macroscopic porosity stabilizing at 73%, and the micropore diameter converging to 5.5 μm. The data from this example not only conforms to the laws of polymer rheology but also reversely verifies that the material disclosed in this invention can still resist the thermal collapse of the overall structure and maintain excellent radio frequency transmission stability under extreme thermal stress.
[0059] 4. In Comparative Example 3, when the forced axial mechanical tensile stress of 0.5 MPa or even higher is released during the setting period at 380°C, exceeding the critical melting point, the micro- and nano-molecular chain segments, which have been forcibly elongated by the previous mechanical stretching and stored extremely high elastic internal energy, will release stress and undergo geometric retraction, causing the entire large mesh structure to collapse and fuse. Macroscopically, this manifests as a large number of micropores in the main insulating layer closing and tending towards re-densification (porosity less than 30%). The distributed capacitance increases sharply, leading to a dielectric constant of 1.98 and an increase in the microwave RF high-frequency loss constant. In contrast, in Comparative Example 5, although tensile stress is provided, its isothermal sintering temperature is below the 327°C melting point (only 300°C). At this temperature, the rigidity of the solid-phase chain segments is physically frozen, preventing free volume expansion and diffusion to complete the interfacial chain penetration and molecular entanglement fusion. Forced cold pressing results in an adhesion test of only 1.2 N, and the wire sheath is easily pulled off.
[0060] The foregoing detailed and systematically described the basic scientific principles, core chemical structural features, and significant technical advantages of this invention compared to existing processes. Those skilled in the art should fully understand that the essence and spirit of this invention are by no means limited to the specific embodiments listed above. All embodiments, without departing from the core concept of this invention, should fall equivalently within and be fully covered by the strict protection claimed in the appended claims.
Claims
1. A stretched foam insulation structure parallel to a copper cable, characterized in that, From the inside out, the following are included: Two parallel metal conductors; A dense inner layer is coaxially and directly coated on the surface of each of the metal conductors. The dense inner layer is an extrusion of modified polytetrafluoroethylene dispersion resin powder prepared by emulsion polymerization. The modified polytetrafluoroethylene dispersion resin powder extrusion contains perfluoropropyl vinyl ether copolymer units. The mass fraction of the perfluoropropyl vinyl ether copolymer units in the modified polytetrafluoroethylene of the dense inner layer is between 0.3% and 1.5%. The main insulating layer is coaxially and directly wrapped around the outer surface of each of the dense inner layers. The main insulating layer is expanded polytetrafluoroethylene formed by co-extruding and wrapping it on the surface of the metal conductor together with the dense inner layer and inducing phase separation by mechanical longitudinal core stretching. Its microporous skeleton includes polytetrafluoroethylene crystal nodes that have not undergone plastic yielding and microfibers distributed along the tensile stress orientation. The dense inner layer and the main insulating layer have a continuous interface bonding region at the physical interface. The continuous interface bonding region is characterized by the two perfluorocarbon polymer matrices presenting an integrated and continuous molten bonding region at the physical interface without physical phase boundary breaks. A microporous wrapping layer that is spirally wound around and covers the outer periphery of two metal conductors with the main insulating layer on their outer surfaces; A metal shielding layer covering the outside of the microporous wrapping layer; and A polymer sheath layer extruded and coated on the outside of the metal shielding layer. The overall porosity of the main insulating layer is between 33% and 80%, and the average micropore diameter defined by the crystal nodes and microfiber entities is limited to between 0.1 μm and 10.0 μm.
2. The stretched foam insulation structure parallel to the copper cable according to claim 1, characterized in that, The metal conductor is an AWG 26 silver-plated oxygen-free copper single wire. The radial wall thickness of the dense inner layer is set between 0.01 mm and 0.05 mm. The radial wall thickness of the main insulation layer is set between 0.10 mm and 0.50 mm. The peak adhesion force of the single-core axial slip pull-out between the dense inner layer and the metal conductor physical interface is between 5.5 N and 7.8 N.
3. The stretched foam insulation structure parallel to the copper cable according to claim 1, characterized in that, The microporous wrapping layer is made of microporous expanded polytetrafluoroethylene film that has undergone unidirectional or bidirectional stretching and orientation, and its porosity is set to 60% to 90%. The microporous wrapping layer is covered by a spiral overlapping wrapping method, and the interlayer wrapping overlap rate is set to the range of 15% to 50%.
4. The stretched foam insulation structure parallel to the copper cable according to claim 1, characterized in that, The metal shielding layer is a metal foil strip with composite polyester insulating folds on one or both sides, which is wrapped in a spiral manner. The wrapping angle is set to 15° to 45°, and the wrapping overlap rate between the shielding strip layers is between 15% and 30%.
5. The stretched foam insulation structure parallel to the copper cable according to any one of claims 1 to 4, characterized in that, At least one continuous exposed metal drainage ground wire is provided at the circumferential gap on the outside of the microporous wrapping layer; the outer diameter of the metal drainage ground wire is configured to embed and engage with the metal shielding layer under the assembly tension applied by the cabling assembly machine, and the radial physical depth of the ground wire pressed into the porous body of the microporous wrapping layer is controlled to be 10% to 30% of the original total radial thickness of the microporous wrapping layer.
6. A method for processing a stretched foamed insulation structure parallel to a copper cable as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Step S1: Using a double-channel co-extrusion die equipped with a cross-head, a metal conductor whose surface has been uniformly preheated is introduced into the center of the die; a modified polytetrafluoroethylene dispersion resin fine powder paste containing liquid lubricant is pushed into the inner channel of the co-extrusion die to form an inner layer precursor; a standard polytetrafluoroethylene dispersion resin fine powder paste containing liquid lubricant is simultaneously pushed into the outer channel of the co-extrusion die to form an outer layer precursor; the two paste fluids merge in the die outlet sizing zone and are co-extruded on the continuously moving metal conductor surface to form a double-layer bonded unstretched insulating precursor wire; In this extrusion step, the ratio of the cross-sectional area of the extrusion die channel to the final cross-sectional area of the extruded tube is limited to between 100:1 and 200:1; Step S2: The unstretched insulated precursor wire is fed into the heating zone to allow the lubricant components inside the inner and outer precursor layers to evaporate, resulting in a dry double-layer polytetrafluoroethylene insulated wire. Step S3: The dried insulated wire is introduced into the stretching area in a constant temperature field. The longitudinal tensile tension is applied to the core wire by the difference in linear speed of the traction wheel group, so that the longitudinal stretch ratio is controlled between 1.5 times and 5.0 times, and the strain rate is controlled between 50% / s and 150% / s. Step S4: The stretched foamed wire is continuously introduced into a high-temperature sintering heat treatment zone with a temperature higher than the melting point of pure polytetrafluoroethylene crystal phase (327°C) under the external constraint of a constant axial tensile stress of 0.5 MPa to 5.0 MPa in the corresponding cross-section. Step S5: The two insulated wire cores that have been cooled and shaped are brought together in parallel along the plane axis of symmetry. Then, the spiral overlapping wrapping of the microporous wrapping layer, the arrangement and embedding of the metal drainage ground wire, the overlapping wrapping of the metal shielding foil, and the extrusion molding of the outermost polymer sheath layer are completed in sequence.
7. The method for processing a stretched foamed insulation structure parallel to a copper cable according to claim 6, characterized in that, In step S1, the liquid lubricant is defined as an aliphatic hydrocarbon solvent with an initial boiling point and a dry point between 150°C and 200°C, and the mass fraction of the liquid lubricant in the polytetrafluoroethylene paste mixture is between 15% and 25%.
8. The method for processing a stretched foamed insulation structure parallel to a copper cable according to claim 6, characterized in that, In step S4, the steady-state operating temperature of the high-temperature sintering heat treatment zone is controlled between 350°C and 400°C, and the heat treatment residence time of the wire passing through the high-temperature sintering heat treatment zone is controlled between 10 s and 30 s.
Citation Information
Patent Citations
Foamed polytetrafluoroethylene insulated cable and preparation method thereof
CN108461181A
Modified PTFE dispersion resin and preparation method thereof
CN109776821A
